Firms, Labor, Migrations And Unions Within Tomato Value Chain in Southern Italy - Giuseppe D'Onofrio (Ledizioni, 2020)
Italy is the world's third largest producer of industrial tomatoes after US and China and the largest producer in Europe. Sixty percent of production is absorbed by foreign markets such as Germany, UK, France, US, Japan and Russia. In this research work the tomatoes production in Southern Italy is analysed taking into account the restructuring of agriculture in terms of labour and production under neoliberal globalization, the role played by international migrations flows, the structure and the composition of transnational agri-food chains, the rising power of buying alliances in Europe and their price policy vis-à-vis to manufacturers and suppliers. From the countryside of Foggia passing through processing firms in the province of Naples and Salerno until reaching international supermarkets the production and distribution of industrial tomatoes links different firms, places and workers triggering new conflicts and generating new union demands.